2021
DOI: 10.3389/fmed.2021.740987
|View full text |Cite
|
Sign up to set email alerts
|

Screening Referable Diabetic Retinopathy Using a Semi-automated Deep Learning Algorithm Assisted Approach

Abstract: Purpose: To assess the accuracy and efficacy of a semi-automated deep learning algorithm (DLA) assisted approach to detect vision-threatening diabetic retinopathy (DR).Methods: We developed a two-step semi-automated DLA-assisted approach to grade fundus photographs for vision-threatening referable DR. Study images were obtained from the Lingtou Cohort Study, and captured at participant enrollment in 2009–2010 (“baseline images”) and annual follow-up between 2011 and 2017. To begin, a validated DLA automaticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
(30 reference statements)
1
5
0
1
Order By: Relevance
“…From a cost perspective, the total cost per retinal image assessed by AI was $0.017 versus $0.032 per image graded by humans. This result represents a 90.1% cost saving 24. A large sample size of 88,363 images was assessed, further validating the results.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…From a cost perspective, the total cost per retinal image assessed by AI was $0.017 versus $0.032 per image graded by humans. This result represents a 90.1% cost saving 24. A large sample size of 88,363 images was assessed, further validating the results.…”
Section: Resultssupporting
confidence: 63%
“…This result represents a 90.1% cost saving. 24 A large sample size of 88,363 images was assessed, further validating the results. The minimal available CBA evidence on the topic indicates the use of AI in ophthalmology is an economically viable practice with efficacy comparable to human grading.…”
Section: Cost-benefit Analysesmentioning
confidence: 79%
“…In addition, AI technology has been applied to the screening, referral, diagnosis, health care, and follow-up visits of patients with a variety retinal illness. Wang et al [ 33 ] developed a two-step semiautomatic deep learning algorithm–assisted technique to identify fundus pictures and aid in the detection of DR with vision-threatening complications. Optical coherence tomographic (OCT) angiography is a noninvasive imaging technology that may generate angiograms at precise depths within the retina as well as visualize the microvasculature in real time [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…52,53 Recent studies, however, have shown poorer performance of these algorithms in real-world settings. 54 Researchers have also expressed reservations because of a lack of (1) detail in grading, 55 (2) grading of nondiabetic retinal conditions and glaucoma, and (3) an explanation of how the algorithm determines the retinal grade, which often incorporates multiple features from fundus imaging. This technique produces a two-dimensional image that represents the three-dimensional structure of the retina.…”
Section: Technology Needed To Improve the Use Of Ai To Diagnose Diabe...mentioning
confidence: 99%